MODELLING AND NUMERICAL ANALYSIS FOR CRACK PROPAGATION IN COMBINING CONCRETE WITH 25% FEATHER SHELL POWDER USING FINITE ELEMENT METHOD - Nasution, Marah Doly; Syahputra, Muhammad Romi; Rambe, Isnaini Halimah (PATTIMURA UNIVERSITY, 2025)
This study explores the application of the Extended Finite Element Method (XFEM) for modeling fracture behavior, utilizing COMSOL Multiphysics 5.6 to simulate a homogeneous concrete medium without embedded reinforcement. The computational model incorporates key parameters such as stress ratio (Young’s modulus of 137.9 MPa), lateral strain from axial loading (Poisson’s ratio of 0.17), concrete density of 2.4 g/cm³, and a crack growth rate governed by Paris’ law. The simulation results show a maximum stress intensity factor ( ) of 66.2 and a failure point occurring after approximately 22,568 load cycles. A mixture comprising 25% clamshell ash and lime was used as a sustainable cement substitute, achieving a maximum compressive strength of 20.53 MPa—meeting the structural concrete standard. These findings contribute to enhancing predictive fracture models and promoting sustainable material innovation in civil engineering.